Traumatic Injury to the Developing Brain: Emerging Relationship to Early Life Stress - Parker, Kaila N.; Donovan, Michael H.; Smith, Kylee; Noble-Haeusslein, Linda J. (Frontiers in Neurology, 2021)
Despite the high incidence of brain injuries in children, we have yet to fully understand the unique vulnerability of a young brain to an injury and key determinants of long-term recovery. Here we consider how early life stress may influence recovery after an early age brain injury. Studies of early life stress alone reveal persistent structural and functional impairments at adulthood. We consider the interacting pathologies imposed by early life stress and subsequent brain injuries during early brain development as well as at adulthood. This review outlines how early life stress primes the immune cells of the brain and periphery to elicit a heightened response to injury. While the focus of this review is on early age traumatic brain injuries, there is also a consideration of preclinical models of neonatal hypoxia and stroke, as each further speaks to the vulnerability of the brain and reinforces those characteristics that are common across each of these injuries. Lastly, we identify a common mechanistic trend; namely, early life stress worsens outcomes independent of its temporal proximity to a brain injury.